1988
DOI: 10.2135/cropsci1988.0011183x002800050016x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Laboratory Germination Tests and Field Emergence of Maize Inbreds

Abstract: In the USA and Europe, maize (Zea mays L.) is often planted into soils that are or become cold and wet resulting in reduced field emergence, poor stands, and lower economic yields. This study was conducted to determine the relative merits of two germination tests, the cold and soak tests, for prediction of field emergence when soil temperatures are suboptimal for germination. The effects of initial seed moisture on field emergence were also investigated. Field emergence of 48 maize inbred lines was measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 0 publications
3
36
0
1
Order By: Relevance
“…B73 and B49 are considered cold-tolerant whereas G50 and G84 are considered cold-sensitive. Field data on cold tolerance of these inbreds is available (10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…B73 and B49 are considered cold-tolerant whereas G50 and G84 are considered cold-sensitive. Field data on cold tolerance of these inbreds is available (10).…”
Section: Methodsmentioning
confidence: 99%
“…These practices result in slower warming of soils in the early spring compared to more extensive tillage, particularly that done in the previous fall. Thus, physiological characteristics that improve germination and early seedling growth at low temperatures are increasingly of interest to maize producers (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Band eja "te rra " + pa pel (Rush & Neal, 1951); danos causados pelas condições de armazenamento das sementes (Goodsell et al, 1955); danos causados por secagem excessiva (Loeffler et al, 1985;Martin et al, 1988); grau de umidade das sementes (Cal & Obendorf, 1972); injúrias ao pericarpo (Tatum, 1954); tratamento de sementes (Meulen & Henke, 1948;Hoppe, 1956). Dependendo da causa determinante da baixa qualidade das sementes, a resposta poderá ser mais ou menos drástica, dificultando a interpretação dos resultados (Marcos Filho et al, 1987).…”
Section: Resultsunclassified
“…They proposed that, although the saturated cold test is more time consuming than the soak test, it has a higher correlation to field emergence than the soak test (Martin et al, 1988). Martin et al (1988) speculated that the differences between the saturated cold test and the soak test may have originated from damage caused when seed was over dried prior to storage. The authors concluded that lower moisture seed is more sensitive to chilling injury, which decreased saturated cold test germination compared to the soak test.…”
Section: Seed Testingmentioning
confidence: 99%